2010
DOI: 10.4025/actasciagron.v32i2.3702
|View full text |Cite
|
Sign up to set email alerts
|

Armazenagem de morangos cv. Camarosa e cv. Verão em atmosfera modificada

Abstract: ABSTRACT. Modified atmosphere storage of cv. Camarosa and cv. Verão strawberries. Modified atmosphere storage is one of the possibilities to prolong the postharvest shelf life of strawberries. In the present work, four combinations of O 2 and CO 2 concentrations (3 kPa O 2 + 10 kPa CO 2 ; 5 kPa O 2 + 15 kPa CO 2 ; 21 kPa O 2 + 15 kPa CO 2 ; and ambient air) were evaluated along various storage periods. Cv. Camarosa and cv. Verão strawberries (Fragaria x ananassa Duch) were harvested from commercial groves and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
0
1
2
Order By: Relevance
“…According to Chiumarelli and Hubinger (2012), cassava starch-based coatings can assist in reducing water loss, but when relating the increased vitamin C content during storage to the high water loss, it is found that the use of the coating was not effective for this purpose. Some studies report, unlike that observed in the present study, that there is ascorbic acid reduction in stored fruit (Bender et al, 2010;Calegaro;Pezzi;Bender, 2002;Cardoso et al, 2012;Cordenunsi;Nascimento;Lajolo, 2003) and other authors state that the use of different edible coatings can help reduce these losses (Atress et al, 2010;Gol;Patel;Rao, 2013;Wang;Gao, 2013), by promoting gas permeability reduction, thus reducing the respiration rate and consequently the oxidative reactions responsible for ascorbic acid degradation.…”
Section: Resultscontrasting
confidence: 68%
“…According to Chiumarelli and Hubinger (2012), cassava starch-based coatings can assist in reducing water loss, but when relating the increased vitamin C content during storage to the high water loss, it is found that the use of the coating was not effective for this purpose. Some studies report, unlike that observed in the present study, that there is ascorbic acid reduction in stored fruit (Bender et al, 2010;Calegaro;Pezzi;Bender, 2002;Cardoso et al, 2012;Cordenunsi;Nascimento;Lajolo, 2003) and other authors state that the use of different edible coatings can help reduce these losses (Atress et al, 2010;Gol;Patel;Rao, 2013;Wang;Gao, 2013), by promoting gas permeability reduction, thus reducing the respiration rate and consequently the oxidative reactions responsible for ascorbic acid degradation.…”
Section: Resultscontrasting
confidence: 68%
“…Atualmente, as principais formas empregadas para manter a qualidade de frutas e hortaliças estão relacionadas ao uso de embalagens poliméricas, manutenção em ambientes refrigerados, emprego de sanitizantes e aplicação de atmosfera modificada e técnicas de irradiação (BENDER et al, 2010). No entanto, ainda há significativas perdas de qualidade, pois as estratégias e técnicas de manutenção não tem sido suficiente para o processo de preservação.…”
unclassified
“…as amostras acondicionadas em filmes de menor permeabilidade (BOPP) continuaram apresentando as menores médias, como ocorreram nos primeiros 15 dias de armazenamento a 5°C. Tabela 14 -Firmeza (N) de camu-camu armazenado em diferentes embalagens e temperaturas após 15 dias do armazenamento refrigerado PVC -policloreto de vinil, BOPP 20polipropileno biaxialmente orientadode 20 µm de espessura, BOPP 50polipropileno biaxialmente orientadode 50 µm de espessura UR -umidade relativa, DP -desvio padrão, n -número de repetições utilizadas para a análise, CV -coeficiente de variação, (-) representa amostras descartadas por estarem impróprias para comercialização Nota: Para cada análise, médias seguidas pela mesma letra maiúscula na linha e minúscula na coluna não diferem entre si ao nível de 5% de probabilidade pelo Teste de Tukey.As amostras controle em todos os dias de armazenamento e em todas as temperaturas avaliadas apresentaram sempre as maiores médias, o que pode ser justificado pela maior perda de água destes frutos ocasionando assim a diminuição da turgência dos tecidos e a formação de um tecido superficial mais resistente à força de penetração Bender et al (2010). em estudo com atmosfera modificada em morangos, detectaram a resistência da polpa um pouco mais elevada no final do armazenamento e associaram este fato à desidratação da fruta.…”
unclassified